Gerakan Masyarakat Melalui Kearifan Lokal Untuk Meningkatkan Taraf Kelayakan Ekonomi Masyarakat di Era Covid-19 (Dilaksanakan di PT Javas Anugerah Perkasa Bengkulu) - Rachayu, Imma; Maryani, Desy; Selviani, Diah; Lorita, Evi; Wahyudi , Jusuf; Luhtfiah, Izza (Universitas Dehasen Bengkulu, 2021)
This study aims to analyze the role of community movements through the application of local wisdom in increasing the level of economic feasibility of the community in the Covid-19 era. This study was conducted at PT Javas Anugerah Perkasa in Bengkulu. The research method used is primary and secondary data collection involving interviews, observation, and document analysis. The results of the study show that through community movements based on local wisdom, people can overcome the economic challenges they faced during the Covid-19 pandemic. This movement involves utilizing local resources, developing local skills, and promoting local products. In this regard, PT Javas Anugerah Perkasa has played an important role in encouraging community movements and providing support to local initiatives. This study also identified several inhibiting factors that influence the success of community movements, such as lack of access to resources and changes in people's behavior. Therefore, suggested recommendations include increasing access to relevant resources, education and training, as well as ongoing support from the government and related institutions.